Explaining Stagnation in the College Wage Premium - Leila Bengali; Robert G. Valletta; Cindy Zhao (Institute of Labor Economics (IZA), 2025)
After growing substantially during the 1980s through the early 2000s, the college wage premium more recently has been largely unchanged, or stagnant. We extend the canonical production-function model of skill premiums to assess supply and demand contributions to the slowdown in the college wage premium, using annual CPS ASEC data from the early 1960s through 2023. To account for the rising importance of women in the college educated workforce, we estimate a hybrid model that incorporates components that are disaggregated by age and gender. We also allow for non-linearities and changes over time in the parameters of the aggregate production function. Our results suggest that the recent stagnation of the college wage premium primarily reflects demand factors, specifically a slowdown in the pace of skill-biased technological change.
Keywords: I2; J2; J3; 330; college wage premium; educational attainment; labor supply; technological change; worker substitutability